Decentralized variable structure tracking for systems with time-domain dominance - Balluchi, Andrea; Bicchi, Antonio (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we consider the design of tracking controllers for linear MIMO systems described by an input-output model. The presence of known 'weak' interactions among SISO or MIMO subsystems may allow the designer to achieve objectives by using independent controllers of lower complexity than are necessary in general (control decentralization problem).
Keywords: dominance conditions; decentralized control; robust control; variable structure control (VSC)